Thy-1 (CD90) Signaling Preferentially Promotes RORγt Expression and a Th17 Response - Furlong, Suzanne; Coombs, Melanie R. Power; Ghassemi-Rad, Javad; Hoskin, David W. (Frontiers in Cell and Developmental Biology, 2018)
Thy-1 (CD90) is a glycosylphosphatidylinositol-anchored protein (GPI-AP) with signaling properties that is abundant on mouse T cells. Upon antibody-mediated crosslinking, Thy-1 provides a T cell receptor (TcR)-like signal that is sufficient to drive CD4+ T cell proliferation and differentiation into effector cells when costimulatory signals are provided by syngeneic lipopolysaccharide-matured bone marrow-derived dendritic cells. In this study, we investigated the impact of Thy-1 signaling on the production of the T helper (Th) cell subset-associated cytokines, interferon (IFN) γ, interleukin (IL)-4 and IL-17, as well as the in vitro polarization of highly purified resting CD4+ T cells into Th1, Th2, and Th17 cells. Although CD8+ T cells expressed more Thy-1 than CD4+ T cells, both T cell populations were equally responsive to Thy-1 stimulation. In contrast to TcR signaling, which favored IFNγ production, Thy-1 signaling favored IL-17 synthesis and, to a lesser extent, IL-4 production, indicating a previously unidentified difference between the consequences of Thy-1 and TcR signal transduction. Moreover, Thy-1 signaling preferentially induced the Th17-associated transcription factor RORγt in CD4+ T cells. As with TcR signaling, Thy-1 stimulation of CD4+ T cells under the appropriate polarizing conditions resulted in Th1, Th2 or Th17 cell induction and cytokine synthesis that was maintained upon restimulation via Thy-1 or TcR crosslinking. The ability to provide a TcR-like signal capable of promoting T helper cell differentiation and cytokine synthesis was not common to all GPI-APs since cross-linking of Ly6A/E with mitogenic mAb did not promote substantial production of IFNγ, IL-4 or IL-17, although there was a substantial proliferative response. The preferential induction of Th2 and Th17 cytokine synthesis as a consequence of Thy-1 signaling suggests a default T helper cell response that may enhance host defense against extracellular pathogens.